Mithocondrial genetic analyses of the Velence wild carp broos stock candidates - Keszte, Szilvia; Stein, Renáta; Kánainé Sipos, Dóra; Balogh, Erna; Zellei, Ágnes; Sebestyén, András; Balogh, Réka; Guti, Csaba Ferenc; Bokor, Zoltán; Urbányi, Béla; Kovács, Balázs (Animal welfare, Ethology and Housing Systems (AWETH), 2017)
Our aim was to evaluate the genetic diversity of the broodstock candidates of the Velence wild carp (Cyprinus carpio carpio morpha hungaricus) based on mitochondrial DNA sequences, and to develop a cross-breeding plan to maintain or to increase the genetic diversity. 150 specimen were sampled during the experiment and 135 mitochondrial control (D-loop) region DNA sequences were determined. Based on the data 19 maternal line were classified. The most common haplotype (Hap_3) was present in 94 individuals, while the rarest haplotypes (Hap_4, 6, and 19) were present only in one specimen, respectively. Based on the frequency of the genotypes 16 haplotypes (Hap_2, 4-7 and 9-19) are belonging to the rare category. To achieve the greatest genetic diversity within the stock, we recommend crossing 22 individuals from the rare maternal lines with the more common haplotypes. It is worthwhile to implement crossings in as many combinations as possible, to increase the probability of successful conservation of rare maternal lines and genetic backgrounds. But, only those specimens should be selected for breeding that meets the landrace standards and originated from the Lake Velencei. The work was supported by the European Fisheries Fund Fisheries Operative Program III. axis, European Fisheries Fund for Renewable Fisheries provided by the EU and Hungary.
Keywords: carp; diversity; genetics; mitochondrial genome D-loop